Planning effective instruction : - Price, Kay M. (Wadsworth Cengage Learning, 2011)
Planning effective instruction: diversity responsive methods and management, 5th ed., fully equips readers to teach in ways that meet the needs of all students in today's diverse classroom. The four-part organization corresponds with a new framework for diversity responsive teaching that helps focus planning for diversity. Represented by a visual organizer, this framework helps readers see that what they teach, how they teach, and the context for teaching interact to bring about the success of all students.